Addressing Past Injustice, Empowering for the Future? Reparation Policies and ‘Victim’ or ‘Survivor’ Identities in Tolima, Colombia (2023)
Colombia’s Victims and Land Restitution Law of 2011 (Law 1448) has established an ambitious reparation framework. Using primary data from six municipalities in Tolima, we highlight how the limited realisation of Law 1448’s transformative aspirations has contributed to a complex co-existence of ‘victim’ and ‘survivor’ identities. We argue that this pattern reflects the ambiguities of a reparation framework that emphasises the transformation of victims into empowered agents but struggles to fulfil its promises due to insufficient resources. To fully understand pitfalls and opportunities of transformative justice, researchers need to pay closer attention to its impact on people’s everyday survival strategies.